2002
DOI: 10.1159/000067168
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Thermography in Newborns: The First Hour after Birth

Abstract: Objective: It was the aim of this study to investigate the surface temperature in newborns within the first hour after delivery. Furthermore, the influence of different environmental conditions with regard to surface temperature was documented. Methods: Body surface temperature was recorded under several environmental conditions by use of infrared thermography. 42 newborns, all delivered at term and with weight appropriate for date, were investigated under controlled conditions. Results: The surface temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 13 publications
0
22
0
4
Order By: Relevance
“…6,8 In healthy newborns, bathing in warm water may have a beneficial effect on body temperature, leading to a more even temperature profile across the trunk and peripheries. 9 Overall, the consensus is that bathing times can be kept flexible, in line with the characteristics and stability of the newborn, and family preferences. 5 The location of bathing can also vary depending on family preference, and a study comparing bathing by the parent under nursing supervision at the bedside in the first few hours of birth with bathing by a nurse in an admission nursery showed that there was no difference in temperature change between the two groups.…”
Section: First Cleansingmentioning
confidence: 99%
“…6,8 In healthy newborns, bathing in warm water may have a beneficial effect on body temperature, leading to a more even temperature profile across the trunk and peripheries. 9 Overall, the consensus is that bathing times can be kept flexible, in line with the characteristics and stability of the newborn, and family preferences. 5 The location of bathing can also vary depending on family preference, and a study comparing bathing by the parent under nursing supervision at the bedside in the first few hours of birth with bathing by a nurse in an admission nursery showed that there was no difference in temperature change between the two groups.…”
Section: First Cleansingmentioning
confidence: 99%
“…Thermography has been used to assess shunt patency which could be employed in the NICU (Goetz, Foertsch, Schoenberger & Uhl, 2005). Researchers have shown that infrared thermography can be used to study temperature profiles of infants on warming tables, especially for a global picture of body temperature in the delivery room (Christidis et al, 2003). Many other opportunities exist where infrared thermography can be used in the diagnosis and ongoing treatment of skin lesions involving perfusion or lack of blood flow (Saxena & Willital, 2008).…”
Section: 4 Discussionmentioning
confidence: 99%
“…Methods to keep these high-risk babies warm include kangaroo-mother care (skin-to-skin contact) (Ludington-Hoe et al, 2000;Christidis et al, 2003;Dodd, 2005;McCall et al, 2005;Cramer et al, 2005), heated water-filled mattresses (Green-Abate et al, 1994;Gray and Flenady, 2003;Gray et al, 2004;McCall et al, 2005), radiant heaters (Baumgart et al, 1981;Bell, 1983;Bell and Rios, 1983;Seguin and Vieth, 1996;Flenady and Woodgate, 2003;Christidis et al, 2003), and incubators (McCall et al, 2005). More recent studies have demonstrated the effectiveness of occlusive polyethylene wrap to improve admission temperatures and reduce insensible losses in premature infants (Knauth et al, 1989;Vohra et al, 1999Vohra et al, , 2004Bjorklund and Hellstrom-Westas, 2000;Bredemeyer et al, 2005).…”
Section: Thermal Protection Of the Newborn Hypothermia In Newbornmentioning
confidence: 99%